ANALISIS RANGKAIAN LISTRIK DENGAN SISTEM PERSAMAAN LINEAR MENGGUNAKAN DEKOMPOSISI LU - Rahman, Abdul; Juliani, Fitria (Infotronik : Jurnal Teknologi Informasi dan Elektronika, 2024)
The system of linear equations is a topic found in the field of mathematics, which is a branch of algebra. This topic can be implemented in various fields, one of which is in the electrical domain, specifically in electrical circuits. The system of linear equations in electrical circuits is used to analyze the relationships between current and voltage in complex circuits. By applying Kirchhoff's laws, we can formulate equations that represent each element in the circuit. The resulting system of linear equations is then solved using the LU decomposition method. LU decomposition is a technique used to solve systems of linear equations by breaking down the matrix into two components: a lower triangular matrix (L) and an upper triangular matrix (U). The method used to decompose the matrix is the Doolittle method. This article employs matlab as a tool to assist in solving the system of linear equations. Through matlab, this process is automated, enabling quick and accurate analysis of various circuit configurations, such as the obtained results in the discussion  and  which represent the current values flowing through each component.